STUDI TENTANG SEJARAH DAN ASAL-USUL BENTUK MOTIF BATIK JAMBI - suryati, Drs. Muzni Ramanto, Dra. Ernis, M.Pd (Serupa The Journal of Art Education, 2013)
This study aims to : 1) Describe the history of batik Jambi, and 2) to describe the shape of the origins of batik Jambi. This research is a qualitative historical. The data sources are the primary source directly by the informant, while secondary data was from the documentation and bibliography. The data was collected through observation, interviews, documentation. The findings of the study were in the 7th century in Kampung Tangah Village and surrounding area, the first time batik was made in Malay Ancient kingdom, the origin of the design motifs such as Tampuk Manggis, Kapal Sanggat, Durian Pecah, Merak Ngeram, Angso Duo, Kuao Berhias, Riangriang, Batanghari, Bungo Kaco Piring, Daun Keladi, Cendawan, Bunga Melati, Bunga Kopi, Keris Siginjai, Bungo Duren. Kata kunci: Sejarah, Asal-Usul, Bentuk, Motif, Batik